Cálculos das propriedades magnéticas, eletrônicas e ópticas da ferrita multiferróica hexagonal LuFeO3 e sua avaliação como material com potencial fotoferroico - Melo, Ailson Tavares de (2022)
The compound LuFeO3 with hexagonal crystal structure (space group P63cm) abbreviated by h-LFO is a magnetoelectric and photoferroic material of great interest to science and new technologies. Despite the many theoretical and experimental studies carried out to date on the properties of this compound, its ground state magnetic structure, band gap energy and optical absorption spectrum are subjects of debate in the literature. Furthermore, recent experimental studies have shown that the efficiency of converting sunlight into electricity of h-LFO is much lower than that of the hexagonal compound LuMnO3 of the same space group (abbreviated by h-LMO) which has optical properties (optical absorption in the visible spectrum, magnitude and nature of the band gap, etc.) and similar ferroelectric properties. In order to contribute to a better understanding of the properties of h-LFO and h-LMO compounds, in this thesis work a systematic investigation of their fundamental properties was carried out. For this study, calculations were performed based on the spin density functional theory implemented in the Elk computational code. The exchange and correlation electronic effects were treated using the so-called local spin density approximation (LSDA) including the effective Hubbard (or Ueff) correction (abbreviated by LSDA + Ueff). For h-LFO, results of calculations with Ueff = 4.0 eV correlated better with experimental facts. The main conclusions are described below. The ground state magnetic configuration is found to be Γ1 + Γ2, which is characterized by weak ferromagnetism along the c-axis (0.07 mB/Fe-atom). The value of the indirect band gap energy is 1.03 eV and the direct band gap energy is 1.06 eV. This band gap energy is due to electronic transitions from the top of the valence band which is characterized by 2p states of the oxygens atoms to the bottom of the conduction band which, in turn, is characterized by 3d states of Fe atoms. The energy transfer in the range between 1.1 and 2.0 eV occurs predominantly within the basal planes of the FeO5 bipyramidal local structure. This fact explains the high absorption of light polarized perpendicularly to the hexagonal c axis in relation to the directions parallel to it that were observed in thin both calculated and experimental spectra. Comparisons of the mean values of the effective mass tensor of the h-LFO and h-LMO calculated at certain points of high symmetry in the Brillouin zone, as well as the values of exciton binding energies in these compounds, allowed us to explain the experimental results that demonstrate that the photoconversion in the h-LMO is greater than in the h-LFO. The calculations showed that the values of the effective masses of the charge carriers in h-LFO are higher than those in h-LMO. In addition, the values of binding energies of photogenerated electronhole pairs in h-LFO are also higher in h-LFO than in h-LMO. These two facts, therefore, lead to a lower mobility of charge carriers in the material, contributing significantly to the low photoconversion efficiency in h-LFO compared to h-LMO. Another important conclusion obtained is that there is a high anisotropy of the electron photocurrent in both compounds due to the fact that the values of the effective electron masses are much larger along the crystalline c axis direction than those along any direction within of the crystalline ab plane.